Treasured Polish folk rhymes, songs, and games : from Kolzalki opalki, rhymes, songs, and games - Rogoszowna, Zofia; Gramatyka-Ostrowska, Anna.; Colonny-Walewski, Stanislaw; Polanie Club (Minneapolis, Minn.) (Minneapolis : Polanie Pub. Co., 1976)
A collection of folk rhymes, songs, and games in Polish and English. Ages 5-12.
In part with music, for voices and piano.
Keywords: Children's songs, Polish; Singing games; Folk songs, Polish